On the Welfare Effects of Foreign Investment - Balcão Reis, Ana (2019)
Modern growth theory emphasizes endogenous technological change as the engine of growth. A policy implication for developing countries that has been drawn from this theory is that foreign direct investment increases growth. Foreign producers with more advanced technology increase the rate of innovation and the rate of growth of GDP. In this paper we show that, given the knowledge spillovers and creative destruction effects existent in these models, even for a closed economy, an increase in the rate of growth does not always imply an increase in welfare, there may be an immiserizing growth effect. In an open economy welfare assessments must, also, recognize that national investment may become unprofitable due to foreign competition. Taking into account all the relevant effects, we characterize the conditions that imply a positive or a negative welfare effect.